2020
DOI: 10.15184/aqy.2020.4
|View full text |Cite
|
Sign up to set email alerts
|

Phoenician lime for Phoenician wine: Iron Age plaster from a wine press at Tell el-Burak, Lebanon

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In the coastal areas of the Levant, near the present-day city of Jaffa (10th-9th century BC), for example, where there was no bedrock, the basins were made of plaster mixed with crushed shells [26]. In southern Lebanon, the wine-archaeological site of Tell el-Burak (8th-6th century BC) demonstrates the early use of lime plaster by contemporary Phoenicians, who flourished roughly between 1500-300 BC [27]. In an even simpler device, treading could be done in portable clay floors or tubs [28].…”
Section: The Basic Rock-cut Field Treading Installationmentioning
confidence: 99%
“…In the coastal areas of the Levant, near the present-day city of Jaffa (10th-9th century BC), for example, where there was no bedrock, the basins were made of plaster mixed with crushed shells [26]. In southern Lebanon, the wine-archaeological site of Tell el-Burak (8th-6th century BC) demonstrates the early use of lime plaster by contemporary Phoenicians, who flourished roughly between 1500-300 BC [27]. In an even simpler device, treading could be done in portable clay floors or tubs [28].…”
Section: The Basic Rock-cut Field Treading Installationmentioning
confidence: 99%
“…The Iron Age wine production, storage and consumption are evidenced by the variety of transport containers (amphorae) in large quantities and wellknown structures (e.g., presses, masonry vats, storage facilities and equipment) associated with wine or olive oil production [70,160]. particular, excavations at the coastal site of Tell el-Burak have revealed a well-preserved 2600-year-old Phoenician wine press, considered as the first Iron Age wine press in modern-day Lebanon [119]. The Phoenician civilization was founded on the trade of valuable goods and merchant activities from the cities located in contemporary Lebanon and flourished between 1500 and 300 BC.…”
Section: From the Levant To The Italian Peninsulamentioning
confidence: 99%
“…These are only a few of many testimonies praising the renown and evoking the oldness of wine production in Lebanon, while modern archaeological and scientific evidence have backed up ancient literature. The discovery of shipwrecks from the 8th century BC carrying Phoenician wines from Tyr [ 3 ] and the recent unearthing of an iron-age plaster from a Lebanese wine press [ 4 ] date the production of Lebanese wines back to the Phoenician era at least. On another level, genetic studies have suggested that the Lebanese oenological Saccharomyces cerevisiae flora seems to be ancestral to other worldwide oenological floras [ 5 ].…”
Section: Introductionmentioning
confidence: 99%